2020
DOI: 10.1080/26395940.2019.1710260
|View full text |Cite
|
Sign up to set email alerts
|

Straw input can parallelly influence the bacterial and chemical characteristics of maize rhizosphere

Abstract: The effects of straw input, including three strategies: chopped straw, straw-derived compost and biochar, on bacterial communities and chemical composition in maize rhizosphere were investigated according to a three-year field experiment. Illumina MiSeq sequencing showed that biochar input increased bacterial richness but decreased bacterial diversity in rhizosphere when compared with the results from no straw control. The functional prediction of Kyoto Encyclopedia of Genes and Genome pathways confirmed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
0
11
1
Order By: Relevance
“…Acidobacteria was not the dominant population with respect to the chiA gene community. Our previous study found that Acidobacteria formed the second largest group of bacteria, and stover treatments decreased its abundance (Li et al, 2020). Banerjee et al (2016) also pointed out that Acidobacteria were the keystone taxa during organic matter decomposition in arable soil.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Acidobacteria was not the dominant population with respect to the chiA gene community. Our previous study found that Acidobacteria formed the second largest group of bacteria, and stover treatments decreased its abundance (Li et al, 2020). Banerjee et al (2016) also pointed out that Acidobacteria were the keystone taxa during organic matter decomposition in arable soil.…”
Section: Discussionmentioning
confidence: 94%
“…Sun et al (2015) pointed out that higher bacterial diversity was observed with organic matter than with chemical fertilizer alone. We propose that higher bacterial diversity might be responsible for the increase in the chiA gene diversity, while our study about the response of soil bacterial richness and diversity in the rhizosphere was different with the chiA gene (Li et al, 2020). We should thoroughly study the relationship between the chitinase gene and bacteria in rhizosphere soil and bulk soil.…”
Section: Relationship Between the Soil Chia Gene Community Compositio...mentioning
confidence: 84%
See 2 more Smart Citations
“…Short-term fertilizer addition decreased microbial diversity but increased species richness, which was inconstant with former studies. 39 , 40 …”
Section: Resultsmentioning
confidence: 99%